2012
DOI: 10.1093/bja/aes203
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound description of a superior laryngeal nerve space as an anatomical basis for echoguided regional anaesthesia

Abstract: I.V. access was obtained and ECG, pulse oximetry, and continuous invasive arterial pressure monitoring were established. The patient was placed in the right lateral position and commenced on NIV. The insertion of the intrathecal catheter was technically difficult, and the epidural space was located with a 16 G Tuohy and the use of the image intensifier and contrast. A dural tap was achieved at 7 cm and an intrathecal catheter inserted to 11 cm. After incremental titration with 5 ml of levobupivacaine 0.25%, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…[7][8][9] In cadavers, it is possible to simulate ultrasound-guided superior laryngeal nerve blockade and demonstrate dye placement around the nerve by placing the injectate either near the hyoid bone or directly onto the nerve. [8][9][10] Consistent sonographic visualization of the superior laryngeal nerve in patients however continues to be a challenge. 11 This case series demonstrated that effective ultrasoundguided superior laryngeal nerve block can be achieved in patients who require awake fiberoptic intubation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] In cadavers, it is possible to simulate ultrasound-guided superior laryngeal nerve blockade and demonstrate dye placement around the nerve by placing the injectate either near the hyoid bone or directly onto the nerve. [8][9][10] Consistent sonographic visualization of the superior laryngeal nerve in patients however continues to be a challenge. 11 This case series demonstrated that effective ultrasoundguided superior laryngeal nerve block can be achieved in patients who require awake fiberoptic intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, ultrasonographic visualization of the superior laryngeal nerve has not been possible due to its small size (1 mm diameter in most cases) and the limited resolution capabilities of most ultrasound imaging systems. [10][11][12] Relatively new improvements in ultrasound imaging technology have resulted in commercially available ultrasound probes that offer higher resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography (US) has already been applied in assisting the performance of iSLN block, however, yielding conflicting results. Barberet et al, for instance, describe a 'SLN space' as an anatomical basis for echo-guided SLN block after being unable to identify the SLN in 100 volunteers using a 12 MHz linear probe 18 . They could not exclude the nerve being present in the SLN space, defined by them to be located between the hyoid bone superiorly, thyroid cartilage inferiorly, thyrohyoid muscle anteriorly and thyrohyoid membrane posteriorly -the structures optimally visualized in 81% of their scans.…”
Section: Tatjana Stopar Pintaričmentioning
confidence: 99%
“…Initially, authors had suggested depositing the drug in superior laryngeal space. [2] Lately in a case series by Sawka et al ., they successfully visualized the SLN and accurately placed local anesthetic around it followed by AFOI. [3]…”
mentioning
confidence: 99%